Discourses of flood disaster preparedness by NGOs: humanitarian aid, teamwork and victimization - Selvaraj S.,; Sandaran S.C., (Penerbit Universiti Kebangsaan Malaysia, 2019)
In recent years global warming and climate change due to human activity and natural phenomena, have become recognized as major contributors to the increased occurrence of flood events worldwide. Similarly, the frequency and seriousness of floods in Malaysia have made it a major threat to the country. To this end, research on flood disaster has increased. Most investigations have however, focused on engineering fields, thus there is a real need for research on human activities, response and involvement. Addressing the need for research on human involvement in flood, we adopt a social constructionist perspective to investigate the discursive construction of knowledge about flood disaster preparedness by NGOs commonly involved in flood mitigation and management in Johor. We draw on the perspective that disaster discourses reveal interpretations and perceptions of ways of understanding flood disaster, and that different discourses directly shape and influence response and action for flood mitigation and management. The data consists of four in-depth semi-structured interviews with officers from various NGOs. Adopting van Leeuwen’s Critical Discourse Analytic approach, i.e. recontextualisation if social practice and representation of social actors and social action, the findings show that the members from NGOs employ various discourses such as discourses of flood causation, discourses of teamwork and humanitarian which have a direct impact on their actions/ response during the floods. More specifically, these discourses highlight more of what they do rather than the communities being helped. The study posits that the discourses not only show the positioning of the NGOs as humanitarians called on to help others, but via a discourse of victimization, they construct flood risk communities as helpless victims awaiting assistance. It advocates a change in mindset of the various parties involved in flood disaster mitigation and management in Malaysia, from that of perceiving the community as victims to survivors, thereby tapping on the communities’ resourcefulness via discourses of empowerment, communitarianism and responsibilization.